2021
DOI: 10.1172/jci.insight.93382
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid cell modulation by a GLP-1 receptor agonist regulates retinal angiogenesis in ischemic retinopathy

Abstract: Ischemic retinopathies including diabetic retinopathy are major causes of blindness. While neurons and Müller glia are recognized as important regulators of reparative and pathologic angiogenesis, the role of mononuclear phagocytes (MPs), such as microglia/macrophages, is unclear, particularly microglia, the resident retinal immune cells. Here we found microglial/macrophage activation in human diabetic retinopathy, especially in neovessels from human neovascular membranes in proliferative retinopathy, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Inflammatory processes in the retina do not only propagate local cell stress and apoptosis induction, but they also have the potential to activate and attract mononuclear phagocytes (MPs). Indeed, several works have shown that the number of MPs in the retina increases during the course of the OIR model and that these cells accumulate especially in areas of ischemia and neovascularization, which is suggestive of a possible role for MPs in IR [ 10 , 24 , 27 , 51 , 73 , 74 , 124 ]. In fact, some studies have identified retinal MPs as key modulators of neovascularization [ 73 ].…”
Section: Ischemic Retinopathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory processes in the retina do not only propagate local cell stress and apoptosis induction, but they also have the potential to activate and attract mononuclear phagocytes (MPs). Indeed, several works have shown that the number of MPs in the retina increases during the course of the OIR model and that these cells accumulate especially in areas of ischemia and neovascularization, which is suggestive of a possible role for MPs in IR [ 10 , 24 , 27 , 51 , 73 , 74 , 124 ]. In fact, some studies have identified retinal MPs as key modulators of neovascularization [ 73 ].…”
Section: Ischemic Retinopathiesmentioning
confidence: 99%
“…However, as the delicate retinal homeostasis is unbalanced during IR development and cell stress and inflammation manifest in the tissue, microglia detect these changes and become activated. Microglial activation has indeed been documented in clinical studies from patients with IR [ 3 , 18 , 122 , 124 ], as well as in the mouse model of OIR [ 10 , 32 , 73 ]. The activation of microglia in the retina is a tightly regulated process that involves changes in their morphology, migration, proliferation, cytokine secretion, and phagocytic activity and can be either beneficial or harmful to the retina [ 1 , 10 , 53 ].…”
Section: Ischemic Retinopathiesmentioning
confidence: 99%
“…Beneficial effects of activation of GLP-1R in diabetic models involve both functional and morphological aspects, and result in prevention of BRB breakdown [ 47 ], preservation of retinal thickness [ 59 ], inhibition of macrophages infiltration and activation [ 60 ], prevention of retinal neurodegeneration [ 53 , 58 , 61 ], of loss of pericytes [ 62 ], and of the loss of b-wave amplitude [ 62 , 63 , 64 ].…”
Section: Anti-inflammatory Effects Of Glp-1 In the Retinamentioning
confidence: 99%
“…Activation of microglia and astrocytes plays an important role in the pathogenesis of glaucoma [ 73 ]. Interestingly, the DPP-IV inhibitor linagliptin and the long-acting GLP-1R agonist NLY01 were able to reduce activation of microglia during gliosis in STZ-diabetic rats [ 60 , 62 ]. In particular, NLY01 reduces the release from the microglia of mouse of proinflammatory cytokines (C1q, TNF-α, and IL-1α) involved in the progression of glaucoma [ 53 , 75 , 76 , 77 , 93 ].…”
Section: Retinal Ganglion Cells and Muller Cellsmentioning
confidence: 99%
“…Proliferative retinopathies (PRs), which are primarily characterized as pathological retinal angiogenesis, are the leading cause of irreversible blindness in individuals of all age groups, including retinopathy of prematurity (ROP) in childhood, proliferative diabetic retinopathy (PDR) in middle-age adults, and age-related macular degeneration in the elderly ( 1 3 ). Accumulating evidence implicates mononuclear phagocytes (MPs), such as microglia, infiltrated monocytes, and monocyte-derived macrophages, in the regulation of pathological ocular neovascularization ( 4 7 ). Among the MPs, microglia are the resident myeloid cells of the CNS, encompassing both brain and retina ( 8 11 ).…”
Section: Introductionmentioning
confidence: 99%